PROFILE OF ACADEMIC PROCRASTINATION OF FINAL STATE COLLEGE STUDENTS OF PGRI ADIBUANA UNIVERSITY SURABAYA - Sofiea Cameilya Putri; Muwakhidah Muwakhidah; Ariella Candraningtyas Sari; Chybha Aulindra Mawardyah (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
Academic procrastination is a tendency to postpone or start an academic assignment. The main objective of quantitative research is to explain the relationship between the variables studied using statistical techniques. Using a quantitative approach to the type of descriptive approach. Subjects were 27 final year students at Adi Buana University, Surabaya, who were selected through random sampling. While the research instrument used a procrastination questionnaire which adopted from Ahmaini 2010. Analysis of research data used descriptive statistical analysis techniques. The results showed that the final year students, the very high category reached a total of 20 students with a percentage of 74.07% and the low category reached a total of 7 students with a percentage of 35.92%. The Emotional Distress indicator has the highest presentation, namely 29.62%, Perceived Ability has a percentage of 25.92%, Perceived Time has a percentage of 25.92%, and the Intention Action Gap indicator has the lowest percentage, namely 18.51%. Thus the procrastination of final year students is in a very high category. This research data shows the development of students who need responsive services related to academic procrastination of final year students.